IMPACT OF GLOBALIZATION ON AGRICULTURAL FOREIGN TRADE OF SELECTED DEVELOPING COUNTRIES (1995-2017) - Ghazal, K. N.; Qasim, R. S.; Sabah, O. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Since the 1990s, the world has undergone dramatic and rapid changes towards the globalization of economic life. The research aims to examine theoretical frameworks and empirical studies that analyses and interpret the mechanism and channels of the impact of globalization policies on agricultural foreign trade by adopting an objective pilot model capable of diagnosing the nature value and direction of this impact based on the latest techniques used in the analysis of time series and the most important tests thereof, namely, both the unit roots test and (E-views 10) program for three developing countries Malaysia, Thailand, and Turkey, during the period 1995-2017. The results of the estimate have shown that there is appositive and statistically significant impact on agricultural foreign trade in the long and short term of the two countries of Malaysia and Thailand, while the relationship was only moral in the short term for Turkey.